miRNome profile in blood samples upstream and downstream of the coronary lesion and arterial aortic root before and after angioplasty in subjects with chronic and acute coronary syndrome: A pilot observational study protocol (Plaque study) - Olga Protic; Anna Rita Bonfigli; Fabiola Olivieri; Adrianapia Maria Lamedica; Gabriele Gabrielli; Roberto Antonicelli (PLoS ONE, 2025)
Currently the mechanisms that lead an atherosclerotic plaque to become unstable and those that trigger the coagulative/thrombotic processes leading to acute coronary syndrome have yet to be clarified. It has been suggested a possible role of microRNAs in the physiopathology of the atherosclerotic process related to acute and chronic ischemic cardiomyopathy. However, no data exists on the correlation between microRNAs expression in coronary (upstream and downstream of the coronary lesion) and arterial (at the aortic root level) blood from patients with acute coronary syndromes (ACS) and chronic coronary syndromes (CCS) before and after angioplasty. The study’s primary objective is to assess miRnome analysis in coronary and arterial blood sampling in ACS and CCS patients before and after angioplasty. The secondary objective is to analyze interleukin-6 and soluble ST2 levels in the peripheral plasma samples before and after angioplasty. Ten patients with ACS and ten patients with CCS will be enrolled. Coronary stenosis treated with angioplasty will be located in the proximal segments of the three main vessels: the anterior interventricular artery, the circumflex artery, and the right coronary artery. The angioplasty procedure will be performed according to standard clinical practice. Before and after angioplasty, blood samples upstream and downstream of the coronary lesion will be taken, arterial sampling at the aortic root level will be performed, and peripheral venous blood will be collected. The expression of serum microRNAs will be analyzed by Next-generation sequencing. Quantitative analysis of pro- and anti-inflammatory molecules such as interleukin-6 and the soluble form of the soluble ST2 will be performed on various blood samples. This study is registered in ClinicalTrials.Gov on October 30, 2023 (ID NCT06103357).